Subjectivity and social resistance: a theoretical analysis of the Matrix Trilogy - Jamal, Ahmad (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2017)
The Matrix (1999) is a science-fiction film that successfully bridges modern cinematic action sequences with philosophical parables. It recalls the tradition of philosophical elaboration through science-fiction narratives; a tradition that has existed since the time of Plato. This study aims to bridge the divide between philosophy and psychology by using a theoretical analysis to discuss and explore the ideas of social thinkers (featured in the Matrix Trilogy) and critically analyse them alongside established psychological theories. More specifically, this study provides an in-depth and critical exploration of the ways in which the philosophical works of Jean Baudrillard and Karl Marx, and the widely used and recognised psychological perspectives on human development, cognition and learning offered by both Urie Broffenbrenner and Jean Piaget to simultaneously elucidate a model of human subjectivity and development in today's techno- consumerist society with specific attention to critical resistance. This study suggests that with the rise of the internet and modern communication media; sociocultural and political issues that Broffenbrenner conceptualised as existing in the macrosystem, now have a presence in the microsystem, and correspond to Broffenbrenner's requirements as to what constitutes a proximal process. These processes, according to Broffenbrenner, have the most longstanding effects on our development and contribute the most to our personality. This study also argues that the pre-operational stage and the process of symbolisation both of which Piaget identified are important phases in the child's life that see the accrual and development of signs and discourses. These signs and discourses then contribute to the development of our mind's cognitive structures which Piaget called schema. These structures are developed as we grow and help us make sense of the world by processing information and organising our experiences. This would mean that we perceive and interpret our world through ideologically shaped mental structures. These findings stress the importance of ideological influences and their impact on development and hearken more closely towards ideas about the presence and the effects of ideology by thinkers like Plato and Marx, as well as the dystopian futures explored in science-fiction media like the Matrix Trilogy, George Orwell's 1984 (1948) and Aldous Huxley's A Brave New World (1932), and also the options for critical social resistance explored in the narratives and heroic deeds of these books and their characters.
Keywords: Matrix (Motion picture); Matrix reloaded (Motion picture); Matrix revolution (Motion picture) Baudrillard, Jean, 1929-2007. Simulacres et Simulation; Science fiction -- Philosophy; Mass media -- Social aspects; Culture in motion pictures; Dystopian films